N. sphaeroides phycocyanin subunit Ns-α and Ns-β improve C. elegans antioxidative capacity via ROS-related regulation - Wu,Xiaoyu; Zhang,Caiyun; Zhou,Shuwen; Cheng,Chao; Fang,Qing (PeerJ, 2025)
Oxidative stress and damage to macromolecules due to free radicals such as reactive oxygen species (ROS) are commonly considered factors that can impair health. This study investigated the potential antioxidant properties of of two subunit proteins associated with the pigment-protein complex phycocyanin derived from Nostoc sphaeroides (Gexianmi). Bacterial expression vectors were separately constructed to induce the two engineering subunit proteins, Ns-α and Ns-β. These engineering proteins were then examined for their potential to enhance antioxidative capacity in Caenorhabditis elegans. Firstly, a proper concentration of the proteins Ns-α and Ns-β in vitro exhibited 2, 2-azino-bis 3-ethylbenzothiazoline-6-sulfonic acid (ABTS) radical scavenging activity. Secondly, while there were no other observed effects on the nematodes, those treated with the proteins showed significant improvements in motility and reduced levels of lipofuscin compared to the control group. Furthermore, thirdly, the treated nematodes demonstrated increased resistance to oxidation, as evidenced by the higher survivals under oxidative conditions induced by 5 mM H2O2. Notably, the treated nematodes exhibited decline in endogenous ROS levels, and the redox-related genes, such as SOD-3 and CAT-1, were down-regulated following consumption of the engineering proteins. Taken together, these findings suggest that engineering proteins Ns-α and Ns-β improve the antioxidative capacity of C. elegans by modulating ROS-related regulation, making them potential modulators in responding to oxidative stressors.
Keywords: N. sphaeroides; Phycocyanin; Antioxidation; Protein; C. elegans